Oil Price Shocks and Economic Growth in Nigeria: Are Thresholds important? (2011)
The impact of oil price shocks on the economy has occupied the attention of researchers for almost four decades. Majority of studies support the existence of a negative association, while some recent evidences seem to have popularised the view that outcomes are the artefacts of misspecified functional forms. This study, although similar in spirit to this popular opinion, is, however, distinct in a number of ways. Firstly, unlike most Nigeria-specific studies, this paper explores alternative measures of oil price shocks, which have been developed and used in the literature with a view to ascertaining the extent to which conclusions about the oil price-growth association depend on the definition of shocks adopted. More importantly, this, to the best of our knowledge, is a pioneer attempt at introducing threshold effects into the linkage between oil price shocks and output growth in Nigeria. The relatively recent regime-dependent multivariate threshold autoregressive model, together with the characteristic impulse response functions and forecast error variance decomposition, is adopted in this study. Using quarterly data spanning 1985–2008, a non-linear model of oil price shocks and economic growth is estimated. Our main results indicate that oil price shocks do not account for a significant proportion of Observed movements in macroeconomic aggregates. This pattern persists despite the introduction of threshold effects. This implied the enclave nature of Nigeria’s oil sector with weak linkages. Therefore, the need to spend oil revenue productively is imperative if favourable effect on real output growth is envisaged.